High BCAA Enteral Food Formulation Based on Local Food Elakati (Pumpkin Enteral, Red Beans, and Egg White) for Liver Cirrhosis Patients - Sheila Amara Putri; Fahdah Haniyah; Annisa Failasufa; Aprodhit Justicia Nabila; Umi Kurniawati; Fitriana Mustikaningrum (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Liver cirrhosis is a chronic disease often accompanied by malnutrition due to an imbalance of amino acids, requiring nutritional interventions such as affordable, locally sourced enteral formulas high in Branched Chain Amino Acids (BCAA). Objective: To develop a high-BCAA enteral formula using pumpkin, red beans, and egg whites. Methods: This study used an experimental design. Nutritional content was assessed empirically; viscosity was measured with a viscometer, osmolality with an osmometer, flow rate using a nasogastric tube, organoleptic tests by 15 panelists, and food cost calculated through market surveys. Organoleptic data were analyzed using the Kruskal-Wallis and Mann-Whitney tests (p<0.05). Results: The formula had an energy density of 1.13 kcal/ml (F1) and 1.07 kcal/ml (F2), with nutrient content meeting the standards. Viscosity for F1 and F2 exceeded recommended levels; average flow rates were 0.08 and 0.18 cc/second, respectively. Osmolality of F1 met enteral nutrition recommendations and no sediment was found. Organoleptic tests showed significant differences between CEF, F1 and F2 in color (p=0.001), aroma (p=0.008), texture (p=0.018), and overall acceptance (p=0.034), but not in taste (p=0.184). Conclusion: ELAKATI F1 is recommended as a high-BCAA enteral formula due to its nutritional adequacy, sensory acceptability, and use of affordable local ingredients.